Pertumbuhan rumput laut Kappaphycus alvarezii yang dibudidayakan bersama Eucheuma denticulatum dengan komposisi berbeda - Pandensolang, Meichel; Salindeho, Indra; Mudeng, Joppy D (Universitas Sam Ratulangi, 2013)
The objective of this study was to determine the growth of seaweed Kappaphycus alvarezii cultivated with Eucheuma denticulatum with different composition. This research was carried out for six weeks, from March to April 2013, in the coastal waters of Sondaken village, Tatapaan District, South Minahasa regency, North Sulawesi. The experiment was designed according to completely randomized design with four treatments and three replications. The four tested treatments were the different composistion of tied seaweed in a long-line raft, where treatment A: 100% K. alvarezii, ; B: 50% K. alvarezii and 50% E. denticulatum, on each culture line, two types of algae were tied in sequence; C: 75% K. alvarezii and 25% E. denticulatum, in which in each line, every three bunch of K. alvarezii was followed by one bunch of E. denticulatum; D: 25% of K. alvarezii and 75% E. denticulatum, on each culture line, every three bunch of E. denticulatum was followed by one bunch of K. alvarezii. Each experimental unit was a 3m x 3,4m rectangular line raft containing four culture lines where the bunch of the tested seaweed were tied. Data collection was performed every two weeks by weighing the tested K alvarezii. The data were statistically analyzed (ANOVA) using JMP statistical program (SAS-institute). The results showed that absolut growth, relative growth and daily growth rate of K. alvarezii was not significantly affected by the tested treatments (Prob> F > 0.5). Thus, the occurence of E. denticulatum in whatever abundance in K. alvarezii cultivation area will not affect the growth of K. alvarezii. Keywords: Seaweed, K. alvarezii, E. denticulatum, growth